Caseous necrosis in cutaneous leishmaniasis. - Peltier, E (1996)
A case of late stage cutaneous leishmaniasis with focal caseous necrosis is reported. The patient, a 30 year old Tunisian man, presented with idiopathic bone marrow aplasia. Microscopically, minimal changes were observed in the epidermis: slight hyperkeratosis and moderate acanthosis. Lesions predominated in the dermis. Epithelioid granulomas were found in the lower dermis. Some of these lesions were clearly surrounded by a ring of lymphocytes and were rarely confluent. A peculiar histological feature was the presence of focal acidophilic and slightly granular necrosis at the centre of some the tuberculoid lesions. Focal fibrinoid necrosis was found in the upper dermis, outside granulomas. A mild to moderate infiltrate of histiocytes, lymphocytes and plasma cells, with scanty neutrophils, was observed mainly in the upper dermis. No intracellular or extracellular Leishman-Donovan bodies were observed. Acid fast mycobacteria, however, were not detected. Leishmaniasis was diagnosed on culture of skin biopsy specimens. The presence of caseous necrosis could lead to diagnostic confusion and result in an erroneous diagnosis of, for example, tuberculosis, syphilis, acne agminata, and sarcoidosis with fibrinoid necrosis. This is especially the case when parasites are scanty or absent.